2019
DOI: 10.1002/nau.24139
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of neurotrophins and transforming growth factor‐β expression in the bladder may lead to nerve hyperplasia and fibrosis in patients with severe ketamine‐associated cystitis

Abstract: Aims To investigate the mechanism of bladder nerve hyperplasia and fibrosis in the patients with ketamine‐associated cystitis (KC). Methods Sixteen patients with severe KC, six patients with mild KC, and five patients with localized invasive bladder cancer served as control patients. Bladder mucosa specimens were taken during the operations, and the specimens were stained for nerve growth factor (NGF) and S‐100 to evaluated nerve hyperplasia. The quantitative Western blot analysis was performed for NGF, brain‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Our previous histopathology study also found nerve hyperplasia and increased collagen deposition in the bladder wall of ketamine cystitis [ 23 , 29 ]. Nerve hyperplasia and fibrosis are histological characteristics of these bladders, and we found that the expression of neurotrophins was significantly correlated with bladder capacity and pain according to the differing clinical severity of ketamine cystitis [ 30 ]. These findings indicate that the upregulation of neurotrophins, transforming growth factor-b, and activation of cell proliferation kinases play an important role in nerve hyperplasia and fibrosis mechanisms in these bladders.…”
Section: P Athophysiologymentioning
confidence: 99%
“…Our previous histopathology study also found nerve hyperplasia and increased collagen deposition in the bladder wall of ketamine cystitis [ 23 , 29 ]. Nerve hyperplasia and fibrosis are histological characteristics of these bladders, and we found that the expression of neurotrophins was significantly correlated with bladder capacity and pain according to the differing clinical severity of ketamine cystitis [ 30 ]. These findings indicate that the upregulation of neurotrophins, transforming growth factor-b, and activation of cell proliferation kinases play an important role in nerve hyperplasia and fibrosis mechanisms in these bladders.…”
Section: P Athophysiologymentioning
confidence: 99%
“…Besides urothelial damage and inflammation, stromal neurogenesis is another important finding 20,52,53 . Prominent nerve bundles and nerve hyperplasia in the deeper portion of the lamina propria or within the detrusor muscle are sometimes evident 20,52 .…”
Section: Evidencementioning
confidence: 99%
“…Neurotrophins are ordinarily present in the bladder and play an important role in the regulation of sensory afferent and urothelium 54 . Upregulation of neurotrophins and their receptors (nerve growth factor, brain‐derived neurotrophic factor, growth‐associated protein 43, and tropomyosin receptor kinase A and B) in bladder mucosa may explain nerve hyperplasia and pain in KC, whereas the increased nerve growth factor expression in the damaged urothelium might suggest a regenerative wound‐healing pattern of the epithelium 52,53,55 . However, different results of serum level of neurotrophins in chronic ketamine abusers have been reported.…”
Section: Evidencementioning
confidence: 99%
“…Bladder fibrosis is a late-stage presentation of bladder outflow tract obstruction (BOO), spinal cord injury (SCI), radiation, or ketamine-induced cystitis [1][2][3]. Bladder fibrosis is characterized by the excessive deposition of the extracellular matrix (ECM), which is composed of collagen (type-I and -III), elastin, and fibronectin.…”
Section: Introductionmentioning
confidence: 99%